CUSTOMER RELATIONSHIP MANAGEMENT – A CASE STUDY IN URBAN WATER UTILITIES IN VIETNAM - Thuy & 6 Others, Tran Thi Thanh (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Customer is the rationale for the existence of any company because a company sells products or services in a relationship with customers. According to Michael LeBoeuf, every company’s greatest assets are its customers, because without customers there is no company. There is no doubt that the better a company can manage its customer relationships, the more success it is likely to have. To facilitate a successful Customer Relationship Management (CRM), there are many CRM tools such as a variety of software provide by different companies. The businesses can choose the most feasible and suitable for their actual situation and capacity. This paper addresses the concept of CRM – what it is, why it is so important, what current trends it has. Not only analyzing CRM from a general perspective, but we also take water utilities in Vietnam as a case study to feature CRM in a more lively and practical way.